(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Epoxy is one of the most widely used polymers used in a variety of applications due to its ‎amorphous structure with a prime hardness and mechanical strength. However, it suffers ‎ from high hardness and brittleness so its flexibility and toughness need to be improved. In this project, an epoxy/polyol blend were prepared with different ‎amounts of polyol (1%, 3%, and 6% wt.). The blends were prepared by mixing epoxy, polyol, and hardener. FTIR, tensile strength, impact strength, hardness, and ‎fracture toughness were used to characterize the blends. Results show that there is ‎no change in the FTIR curves. The results of the mechanical properties show that the tensile ‎strength, elastic modulus, and hardness decreased with polyol addition. Both ‎fracture toughness and impact strength improved with the addition of polyol.‎